Prescription status of oral anticoagulants in patients with acute cerebral infarction with non-valvular atrial fibrillation at the time of stroke onset. Issue 5 (May 2020) - Deguchi, Ichiro; Osada, Takashi; Takao, Masaki
Highlights: Oral anticoagulants (OACs) were prescribed in 42.4% of acute ischemic stroke patients with non-valvular atrial fibrillation. OAC prescription was associated with previous cerebral infarction and specialists. Non-OAC prescription was associated with dementia and antiplatelet drug on admission. Abstract: Background: Anticoagulant therapy is used for preventing cerebral infarction in patients with non-valvular atrial fibrillation (NVAF). However, in clinical practice, many patients with NVAF are not prescribed oral anticoagulants (OACs). In this study, we retrospectively investigated the prescription status of OACs at the time of stroke onset and factors associated with drug prescription. Methods: We studied patients with cerebral infarction with persistent NVAF who were admitted to our hospital between January 1 2015 and December 31, 2018. A total of 245 patients who had a CHADS2 score of 1 or higher and were receiving outpatient care for any underlying disease were included as subjects in this study. Results: Overall, 104 of the 245 (42.4 %) patients received OAC therapy. The percentage of heart failure, percentage of previous cerebral infarction, CHADS2 score before stroke onset, and percentage of specialists (cardiovascular or neurological specialists) were significantly higher in the OAC therapy group than in the non-OAC therapy group. Age was older, and percentages of female sex, dementia, and patients receiving antiplatelet drugs on admission were significantly higher in the non-OAC therapy group than in the OAC therapy group. Multiple logistic regression analysis showed that previous cerebral infarction and specialists were associated with OAC therapy, whereas dementia and antiplatelet drugs on admission were associated with non-OAC therapy [cerebral infarction: odds ratio (OR) 6.926, 95 % confidence interval (CI) 1.742–27.541; specialists: OR 3.209, 95 % CI 1.694–6.080; dementia: OR 0.237, 95 % CI 0.067–0.831; and antiplatelet drug: OR 0.029, 95 % CI 0.007–0.114]. Conclusion: Our findings indicate that OAC prescription is affected by a previous history of cerebral infarction, a history of dementia, concurrent use of antiplatelet drugs, and whether the patient visits a specialist.